Visible light-mediated organophotocatalyzed C–H bond functionalization reactions. Issue 22 (22nd May 2019) - Uygur, Mustafa; García Mancheño, Olga
Abstract : This review provides a current overview of the recent developments in the visible light mediated organophotocatalyzed C–H bond functionalization methodologies. Abstract : Over the last decade, a variety of methodologies for the direct functionalization of C–H bonds have been developed. Among others, visible light photoredox reactions have recently emerged as one of the most efficient and highly selective processes for the direct introduction of a functionality into organic molecules. Easy reaction setups, as well as mild reaction conditions, make this approach superior to other methodologies applying transition metals or strong oxidants, in terms of both costs and substrate and functional group tolerance. In this review, the recent developments in organophotocatalyzed C–H bond functionalization reactions are presented.